Standardization of In-vivo Nitrate Reductase Activity in Mucuna pruriens (L.) DC. Leaves - Chaukiyal, S. P. (Indian Forester, 2008)
The combination of different concentration of substrate (0.025M, 0.050M, 0.075M, 0.10M, 0.15M, 0.20M and 0.25M; KNO3) with different pH of buffer (0.20M KH2PO4 of the pH 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.5, 7.6, 7.7) solutions in two stages were tried for the nitrate reductase activity of Mcuna pruriens Willd. leaves. Maximum nitrate reductase activity was observed in the combination of buffer solution of 0.20M having pH 7.0 and substrate solution of the concentration 0.10M.